Joining forces: Social coalitions and democratic revolutions. (January 2023) - Dahlum, Sirianne
When are mass protest movements able to overthrow authoritarian regimes and promote democratic transitions? This article considers whether socially diverse protest movements are more conducive to democratization than movements restricted to one or a few social groups. Coalitions across social groups should impose higher costs on authoritarian regimes through access to a wide range of resources, strategies and sources of leverage. Heterogenous protest coalitions are also more likely to socially overlap with regime supporters and the security forces, which should encourage regime splits and defections. But, diverse protest movements may also be more vulnerable to fragmentation and in-fighting, which may particularly threaten prospects of democracy in the aftermath of an authoritarian regime breakdown. Analyzing new global data mapping the social group composition of anti-regime protest campaigns from 1900 to 2013, the article finds consistent evidence that socially diverse protest movements are more likely to overthrow authoritarian regimes, and this is not driven by protest size. Socially diverse movements are also more likely to end in the short- and long-run establishment of more democratic institutions, suggesting that heterogenous protest movements' potential for bringing about democracy is more promising than expected. These findings speak to the importance of securing broad and not only large mass movements to promote democracy.